Pro HTML5 Programming Powerful APIs for Richer Internet Application Development - Lubbers, Peter; Albers, Brian; Salim, Frank; Smith, Ric (New York : Apress L. P., 2010)
Annotation HTML5 is here, and with it, web applications take on a power, ease, scalability, and responsiveness like never before. In this book, developers will learn how to use the latest cutting-edge HTML5 web technology—available in the most recent versions of modern browsers—to build web applications with unparalleled functionality, speed, and responsiveness.Explains how to create real-time HTML5 applications that tap the full potential of modern browsersProvides practical, real-world examples of HTML5 features in actionShows which HTML5 features are supported in current browsersCovers all the new HTML5 APIs to get you up to speed quickly with HTML5What you’ll learnHow the HTML5 specification has evolvedHow to develop cutting-edge web applications using new HTML5 features like WebSockets, geolocation, Web Storage, Canvas, and audio and videoWhich features are available in browsers todayWho this book is forWeb designers and developers who want to use the latest cutting-edge technology available in current browsersDevelopers who want to create dynamic, HTML5 web applicationsDevelopers who want to know which HTML5 features are supported in current browsersTable of ContentsOverview of HTML5Using the HTML5 Canvas APIWorking with HTML5 Audio and VideoUsing the HTML5 Geolocation APIUsing the Communication APIsUsing the HTML5 Web Socket APIUsing the HTML5 Forms APIUsing the HTML5 Web Workers APIUsing the HTML5 Web Storage APICreating HTML5 Offline Web ApplicationsThe Future of HTML5